2010
DOI: 10.1108/10867371011085156
|View full text |Cite
|
Sign up to set email alerts
|

Financial liberalization, financial development and growth linkages in Sub‐Saharan African countries

Abstract: Purpose -The purpose of this paper is to use the recent development in unit root tests and cointegration as applied to panel data and dynamic time series, to estimate the relationship between financial liberalization, financial development and growth. Design/methodology/approach -The paper assesses the dynamics of the relationship between financial development, financial liberalization and growth using the latest dynamic panel data framework and time series analyses comprising up to 15 Sub-Saharan African coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 84 publications
(90 reference statements)
3
22
0
1
Order By: Relevance
“…Most of these studies document, in general, a significantly positive role of financial development on economic growth (e.g. Allen and Ndikumana, ; Ghirmay, ; Ahmed, ). However, two recent panel cointegration‐based studies — Fowowe () and Demetriades and James () — have reported that there is no long‐run FG relationship in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies document, in general, a significantly positive role of financial development on economic growth (e.g. Allen and Ndikumana, ; Ghirmay, ; Ahmed, ). However, two recent panel cointegration‐based studies — Fowowe () and Demetriades and James () — have reported that there is no long‐run FG relationship in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Financial liberalization also has an indirect effect on growth. By strengthening and fostering development of the domestic financial sector through imposing discipline on macroeconomic policies, it can lead to a more stable macroeconomic environment (Mirdala, 2006;Ahmed, 2010 The following hypothesis will be tested at 5% level of significance:…”
Section: Data and Variablesmentioning
confidence: 99%
“…It is unnecessary to demonstrate the importance of finance in the process of development, several studies having shown bidirectional links between finances and economic growth (Murinde, 2010;Ahmed, 2010;Akinlo and Egbetunde, 2010). The PAZF development project may only come true only if the status of the currency is prevails in Europe gives a unique opportunity for the political authorities of these countries to take measures likely to favor their monetary independence within the framework of the UA which is to reach a create a unique African currency by 2021.…”
Section: Resultsmentioning
confidence: 99%